Green Technopreneurship Model for Digital Startups Among Gen-Z - Riskia Putra; Fauzan; N. W. Islami Rahayu (ABM: International Journal of Administration, Business and Management, 2025)
This study aims to explore how Gen-Z digital startup founders interpret the concept of green technopreneurship, identify its driving and inhibiting factors, and develop a conceptual model tailored to their context. A qualitative method with a phenomenological approach was employed, involving five Gen-Z founders in Indonesia who run environmentally oriented digital businesses. Thematic analysis revealed key themes such as green values as a business identity, digital technology as a sustainability accelerator, and distinct Gen-Z values such as authenticity and impact-driven work. The study proposes a conceptual model that integrates green values, digital innovation, and youth characteristics as the foundation for developing sustainable startups.